Cultivo de adubos verdes forrageiros em solo previamente irrigado com efluente tratado de laticínio e cultivo em sucessão da alface - Donatti, Ramon Nantes (2016)
The aim of this study was to evaluate the potential for cultivation of forage green manure species in previously irrigated soil with treated dairy effluent, as a phytoremediation technique of sodium, and cultivation in succession of lettuce. The design was in randomized blocks in a factorial scheme, with three sources of water (anaerobic effluent - ANE, aerobic effluent - AE, and tap water - TW) used in beet cultivation, and the post - cultivation of three green forage fertilizers (calopogo, pigeon pea and millet), with four replicates. After the green manure was cultivated the crisp lettuce, cv. "Brida". The following were evaluated: the development of green manures; phytoextraction of nutrients and sodium; the bromatology of the forages, the chemical characteristics of the soil before and after cultivation of green manures; the productivity of lettuce and its chemical characteristics. Millet presented higher fresh shoot mass production (FSMP) when compared to calopogo and millet. However, it showed reduction of FSMP in ANE in relation to TW. In the soil chemical analysis before and after green manuring, it was found that calcium (Ca) and magnesium (Mg) increased after cultivation of green manures. In relation to sodium (Na), millet phytoextracted 22.4 kg ha-1 , differing statistically from pigeon pea (11.4 kg ha-1 ), in the mean of water sources. Millet was the most efficient phytoextractive sodium species, even though no phytoextraction of Na was present at adequate levels so that the soil could receive effluents again. Millet had higher levels of neutral detergent fiber (FDN), acid detergent fiber (FDA) and hemicellulose. Crude protein (CP) did not differ statistically between green manures. In relation to lettuce productivity, there was difference after millet cultivation (2.80 kg m-2 ) in relation to pigeon pea (3.71 kg m-2 ) and calopogo (3.60 kg m-2 ). The lettuce produced satisfactorily after the cultivation of green manures